HUBUNGAN KEPUASAN KERJA DAN LINGKUNGAN KERJA DENGAN MOTIVASI KERJA PEGAWAI PPNPN DI LINGKUNGAN TERMINAL TIPE A PAKUPA SERANG BANTEN - Diyanto, Waluyo; Eliadi Hardian, Dafyar; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
Public transportation business is currently growing rapidly combined with the development of toll road infrastructure that is increasingly developing, the Government and Society currently demand an increase in services in the field of public transportation, so the performance of terminal management services needs to be combined with improving effective and efficient services, so that the terminal can provide quality and professional services. The quality of Human Resources needs to be improved, especially the discipline and work motivation of employees of the Pakupatan Serang Banten Type A Terminal Service Unit. The improvement of the quality and performance of government officials is expected to be seen in the form of service, role models and protection to the community in a good way, the method used in this study is a quantitative survey method with a correlational model. Based on the results of the calculation of the job satisfaction variable, a regression coefficient of 0.629 was obtained. The significance test of the regression coefficient with the t test obtained t count = 7.710 with a significance of 0.000, this means that the job satisfaction variable (X1) has a significant effect on work motivation (Y). The form of this influence is if job satisfaction increases by 1 (one) point while the work environment is considered constant, it will cause an increase in work motivation of 0.629 points. Then the results of the calculation of the work environment variable obtained a regression coefficient of 0.142. The significance test of the regression coefficient with the t-test obtained t count = 2.017 with a significance of 0.046, this means that the work environment variable (X2) has a significant effect on work motivation (Y). The form of this influence is if the work environment increases by 1 (one) point while job satisfaction is considered constant, it will cause an increase in work motivation of 0.142 points. Furthermore, there is a simultaneous influence of the variables of job satisfaction and work environment of: 0.590 or 59.0% on the work motivation of PPNPN employees in the Type A Terminal Environment Pakupatan Serang Banten. While the remaining 41.0% is influenced by other factors that were not studied, such as supervision, work culture, and others, meaning that there is a positive and significant partial influence of the variables of job satisfaction and work environment of PPNPN employees in the Type A Terminal Environment Pakupatan Serang Banten, at t count: 7.710 at Significance (Sig.): 0.000. On the other hand, there is a positive and significant partial influence of the work environment variable on the work motivation of PPNPN employees in the Pakupatan Serang Banten Type A Terminal Environment, at t count: 2.017 at Significance (Sig.): 0.46. Keywords: Job satisfaction, work environment, work motivation.